ANALYSIS OF THE COMPOSITION OF CAPITAL STRUCTURE BY USING ECONOMIC VALUE ADDED (EVA) APPROACH IN TFD A COMPANY - Najmani, Andriani Ratna; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2023)
This research uses case study and aims to evaluate the capital structure of TFD A Company which is a company in the agribusiness industry sector and within the scope of a medium-sized company. During Covid-19 pandemic in 2020-2021, TFD A Company experienced billing difficulties to the manufacturer (buyer). The results of this study show that the EVA value of TFD A Company recorded an increase in negative value but the company still achieved an increase in its net profit. Based on the research of the two comparative companies, it is concluded that the composition of capital structure has its own risks. The implication of this research is that the TFD A Company should consider publicly listing its company, assessed by the composition of the capital structure, the company’s obligations to its shareholders, and the ability to record net income.